Demographic profile of alcohol use disorder patient who received care from a de-addiction centre in central Kerala - C., Maria Babu; P., Maria Joy; Thomas, Ronnie; R., Varghese P.; Kuttichira, Praveenlal (International Journal Of Community Medicine And Public Health, 2020)
Background: The world’s third largest risk factor for disease and disability is alcohol consumption. This is associated with many serious socio-economic issues, including violence, child neglect and abuse, and absenteeism at the workplace. Methods: In this study the socio demographic details of the patients admitted from 1st January 2016 to 31st December 2016 were collected directly from the medical records of a de-addiction centre situated at Thrissur, Kerala. The data was entered to excel and statistical analysis was done by using SPSS 21. A total of 571 cases were included in the study. Results: This study shows that more than half of the patients (52.42%) seeking de-addiction comes under middle age group with the mean age of 42 years. Based on educational category of the patients of this study only 10.4% had graduation and above. The majority of the subjects had either high school certificate or below (84.4%). The educational status of patients was comparable with the pattern among general population. In the present study, 32.9% of the patients are skilled workers. In terms of blood group distribution of the patients, the most observed blood group was O+ (41.4%) followed by B+ (23.9%). Conclusions: Large number of clients seeks help from de-addiction centers. The majority belonged to middle age group and the educational status of patients was comparable with the pattern among general population. There is necessity for further investigation in the de-addiction centers in order to evaluate pattern and trends in misuse of alcohol or substances.